Health-related quality of life in hereditary transthyretin amyloidosis polyneuropathy: a prospective, observational study - Inês, Mónica (2020)
Background Hereditary Transthyretin Amyloidosis Polyneuropathy is a rare life-threatening neurologic disease that imposes considerable mortality and it is associated with progressive related disabilities. In this study, we aimed to assess the effect of the disease across health-related quality of life dimensions, in both carriers of the mutation and patients, to compare health-related quality of life with general population, as well as to explore health-related quality of life prognostic factors among patients, including disease progression and treatment. Methods This study was a multi-institutional, longitudinal, prospective, observational study of hereditary Transthyretin Amyloidosis Polyneuropathy Portuguese adult subjects (621 asymptomatic carriers and 733 symptomatic patients) enrolled in the Transthyretin Amyloidosis Outcomes Survey. Health-related quality of life was captured with the preference-based instrument EQ-5D-3 L. For general population the dataset included all subjects enrolled in a representative national study (n = 1500). Different econometric models were specified; multivariate probit, generalized linear model and generalized estimating equations model; including demographic and clinical covariates. Results Hereditary Transthyretin Amyloidosis Polyneuropathy patients have their health status severely impaired in all quality of life dimensions and more anxiety/depression problems were found among asymptomatic carriers. No differences on utility were found between carriers and general population (p = 0.209). Among patients, the utility value is estimated to be 0.51 (0.021), a decrement of 0.27 as compared with general population utility. Higher disease duration, advanced disease stage and not receiving treatment are associated with impaired health-related quality of life. No differences were found between genders (p = 0.910) or between late (≥50 years) and early-onset patients (p = 0.254). The utility estimate ranged from 0.63 (0.009) in stage I to 0.01 (0.005) in stage IV. Conclusions Hereditary Transthyretin Amyloidosis Polyneuropathy symptoms and progressive associated disabilities substantially decrease patient’s health-related quality of life. Clinical strategies focused on health-related quality of life preservation such as close follow-up of asymptomatic carriers, prompt diagnosis and adequate, early treatment would benefit patient’s long-term outcomes, slowing the progressive decline in health-related quality of life.